Formation of Media Literacy in Teaching Natural Sciences in Primary Grades - G’aniyeva Gulhayo Islom qizi (Researchparks Publishing, 2023)
Today, there is a growing need to implement large-scale reforms in the field of improving the teaching of natural sciences on the basis of multimedia tools, international assessment programs and improving the natural and scientific literacy of students in the classroom. In the UN agreement on education, science and culture